A Case Report :Alprazolam Therapy in A Dextra Fronto-Parietal Meningioma Patient With Anxiety Disorders: Efektivitas Alprazolam Pada Pasien Meningioma Fronto-Parietal Dextra Dengan Gangguan Cemas - Wibowo, Prajogo; Utami, Prawesty Diah (Universitas Muhammadiyah Sidoarjo, 2021)
Meningiomas in the frontoparietal lobe may cause anxiety disorders and panic attacks. While alprazolam is one of the most widely used medications for anxiety disorders, long-term use may result in adverse side effects (withdrawal and rebound effects). This case study aims to describe the efficacy of long-term alprazolam administration in patients with meningiomas for regulating anxiety disorders. Case report :The asymmetrical face is the primary concern of a 65-year-old female when she is anxious. The results of the physical assessment and laboratory tests are within normal ranges. However, The HARS procedure showed moderate anxiety, and the CT scan revealed a meningioma in the right frontoparietal lobe. To regulate patient anxiety disorders, doctors give alprazolam 0.5 mg per day single dose for 4 months and tapering off for 3 months. Conclusion: Long-term administration of alprazolam in these patients can reduce the patient's anxiety disorder without causing withdrawal or rebound effects. A low dosage of alprazolam, a mild level of anxiety illness, and a slow tapering off phase were factors that contributed to the effectiveness of alprazolam treatment to suppress anxiety symptoms in this situation.